The in situ observation of faceted dendrite growth during the directional solidification of GaSb. (15th July 2019) - Shiga, Keiji; Kawano, Masato; Maeda, Kensaku; Morito, Haruhiko; Fujiwara, Kozo
Abstract: In this work, crystal–melt interfaces were directly observed during the directional solidification of molten GaSb having a stoichiometric composition, and the formation of dendrite structures was studied. With increases in growth velocity, the planar crystal–melt interface became unstable and dendrite growth was initiated. Dendrites having {111} facets were found to grow in either the 〈110〉 or 〈112〉 directions, and a pair of twin boundaries was identified at the center of a dendrite. The results show that the growth of dendrites in GaSb is associated with nucleation at twin-related reentrant corners. Graphical abstract: Unlabelled Image